Neuroprotective Effects Of Teneligliptin In An Okadaic Acid-Induced Zebrafish Model Of Alzheimer’s Disease (International Journal of Environmental Sciences, 2025)
This study investigated the neuroprotective effects of Teneligliptin, a DPP-4 inhibitor, in an Okadaic Acid (OA)-induced Alzheimer's disease (AD) in zebrafish model. Zebrafish were exposed to OA to induce AD-like features, followed by treatment with Teneligliptin at concentrations of 8, 16, and 32 mg/L. Behavioral tests revealed that Teneligliptin improved anxiety-like behavior and cognitive deficits induced by OA. Antioxidant assays demonstrated that Teneligliptin restored the activities of SOD, CAT, GSH, and GPx while reducing the levels of MDA and AChE. Histopathological evaluation showed that Teneligliptin mitigated OA-induced brain tissue damage. Additionally, Teneligliptin reduced the expression of BACE1 and PSEN1, indicating its potential to regulate amyloidogenic pathways. Overall, Teneligliptin demonstrated neuroprotective effects by improving behavioral outcomes, restoring antioxidant enzyme activity, and reducing histological damage. These findings support the potential therapeutic use of Teneligliptin in neurodegenerative diseases, in addressing the pathophysiology of AD. The study suggests that Teneligliptin may be a promising agent for the treatment of AD, warranting further investigation.